2017
DOI: 10.21767/2386-5180.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Severe Reversible Form of Chemotherapy Induced Acute Disseminated Leukoencephalopathy: A Case Report with Review of Literature

Abstract: Leuko-encephalopathy is a disease of the white matter of the brain occurring as a result of various exogenous and endogenous causes. It is one rare, but important cause being use of chemotherapeutic agents. Neurological manifestations are numerous with varying severity. Radiological features are characteristic of leukoencephalopathy well depicted on magnetic resonance imaging (MRI). Here the authors describe case of a gentleman with carcinoma rectum undergoing chemotherapy (5 fluorouracil and oxaliplatin) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…There is no literature exploring this question, but it has been reported that ATL development might be dose-dependent. 7 The previous studies state that median time to development of symptoms after 5-FU infusion is 3 days, in our case, it was 4 days. 2 Irinotecan might cause ATL as well, because it is given as a FOLFIRI regimen, it is difficult to know which drug is the causative agent for ATL.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…There is no literature exploring this question, but it has been reported that ATL development might be dose-dependent. 7 The previous studies state that median time to development of symptoms after 5-FU infusion is 3 days, in our case, it was 4 days. 2 Irinotecan might cause ATL as well, because it is given as a FOLFIRI regimen, it is difficult to know which drug is the causative agent for ATL.…”
Section: Discussionsupporting
confidence: 45%
“…There is no literature exploring this question, but it has been reported that ATL development might be dose-dependent. 7 The previous studies state that median time to development of symptoms after 5-FU infusion is 3 days, in our case, it was 4 days. 2…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation